Epoxy resin mold and PDMS microfluidic devices through photopolymer flexographic printing plate - Olmos Carreno, Carol Maritza (2019)
Photopolymer flexographic printing plate is a new photopolymeric material used for microdevices fabrication. This work demonstrates that a photopolymer flexographic master mold can be used for the fabrication of PDMS (polydimethylsiloxane) microdevices by a multi-step manufacturing process. The methodology entails three main fabrication steps: (1) a photopolymer flexographic printing plate mold (FMold) is generated by UV exposure through a transparent film, (2) an epoxy resin mold (ERmold) is fabricated by transferring the features of the photopolymer mold and (3) a PDMS microdevice is manufactured from the epoxy resin mold. The characterization of the manufactured PDMS microdevices was performed using scanning electron microscopy (SEM) and profilometry. Results showed high accuracy in the replication of the profiles. To show the feasibility of the fabrication process a microdevice for microdroplet generation was designed, manufactured and tested. Hence, the manufacturing process described in this work provides an easy, robust, and low-cost strategy that facilitates the scaling-up of microfluidic devices without requiring any sophisticated equipment.